Trabectedin-irinotecan, a potentially promising combination in relapsed desmoplastic small round cell tumor: report of two cases. (17th February 2023) - Ferrari, Andrea; Chiaravalli, Stefano; Bergamaschi, Luca; Nigro, Olga; Livellara, Virginia; Sironi, Giovanna; Gasparini, Patrizia; Pasquali, Sandro; Zaffaroni, Nadia; Stacchiotti, Silvia; Morosi, Carlo; Massimino, Maura; et al.
Abstract: Effective new drugs are urgently needed for desmoplastic small round cell tumor (DSRCT), an extremely rare and aggressive disease with a generally poor prognosis. We describe two heavily-pretreated young patients with advanced-stage DSRCT given third-line treatment with a combination of trabectedin and irinotecan, based on our preclinical data demonstrating its effect on patient-derived xenografts. This trabectedin-irinotecan treatment showed a limited toxicity. One patient had a mixed response (overall stable disease), the other a complete tumor remission. This is the first report of preliminary findings to suggest that combining trabectedin and irinotecan is worth further investigating as a potentially valuable chemotherapy for DSRCT.